2012
DOI: 10.1186/1471-2482-12-s1-s13
|View full text |Cite
|
Sign up to set email alerts
|

The role of atherectomy in the treatment of lower extremity peripheral artery disease

Abstract: BackgroundThe incidence of lower extremity peripheral artery disease (LE-PAD) continues to increase and associated morbidity remains high. Despite the significant development of percutaneous revascularization strategies, over the past decade, LE-PAD still represents a unique challenge for interventional cardiologists and vascular surgeons.MethodTypical features of atherosclerosis that affects peripheral vascular bed (diffuse nature, poor distal runoff, critical limb ischemia, chronic total occlusion) contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 53 publications
(63 reference statements)
1
39
1
Order By: Relevance
“…In randomized trials, atherectomy has been shown to reduce dissection rate and bail-out stenting, 9 minimizing the stent use in longer femoral popliteal lesions. The Jetstream device (Pathway Medical Technologies, Inc., Redmond, WA) is a rotational aspiration atherectomy system that combines rotablation with aspiration capability 10 offering the possibility to debulk the plaque burden within the vessel and decreasing the limitations and complications of traditional angioplasty such as elastic recoil and dissection. 11 However, while in literature few articles show the real safety and efficacy of this device in the early and mid-term period, long-term outcomes are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In randomized trials, atherectomy has been shown to reduce dissection rate and bail-out stenting, 9 minimizing the stent use in longer femoral popliteal lesions. The Jetstream device (Pathway Medical Technologies, Inc., Redmond, WA) is a rotational aspiration atherectomy system that combines rotablation with aspiration capability 10 offering the possibility to debulk the plaque burden within the vessel and decreasing the limitations and complications of traditional angioplasty such as elastic recoil and dissection. 11 However, while in literature few articles show the real safety and efficacy of this device in the early and mid-term period, long-term outcomes are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during percutaneous coronary intervention (PCI) the gold standard treatment, in the vast majority, is the stent implantation as a final step, irrespective of the plaque characterization and vessel wall injuries following lesion preparation. Successful percutaneous revascularization of femoral and popliteal arteries differs from PCI because of the several forces such as torsion, compression, flexion, and extension induced by leg movement 11 These findings might explain the disappointing long-term outcome after peripheral PTA and the high rate of stent fractures at these sites. 12 We believe that in this field, where the role of non-stented techniques such as atherectomy and balloon angioplasty alone, still plays a pivotal role, using an imaging modality able to precisely show the vessel wall response to treatment may provide useful information.…”
Section: Discussionmentioning
confidence: 77%
“…Among them, the treatment strategies for complex lesions such as heavy calcification, long diffuse disease, CTO, and/or previous surgical reconstructions need further improvement. Atherectomy devices or drug-eluting technology have been evolving [7][8][9][10][11][12][13] and are associated with favorable shortand mid-term outcomes. However, these new modalities should be carefully applied after considering the severity of the lesions as well as patient characteristics [10].…”
Section: Discussionmentioning
confidence: 99%
“…In heavily calcified lesions, the EVT approach is difficult and challenging. However, in recent years, a variety of new techniques and devices have become available [7][8][9][10][11][12][13]. The usefulness of high speed rotational atherectomy for calcified lesions is well known and can also be applied to peripheral arteries [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%